Treatment method of enhanced magnesium-aluminum alloy
Through a method including surface cleaning, drying, modification treatment and thermal insulation treatment, the problem of unstable surface performance of magnesium-aluminum alloy is solved, significantly improving its surface stability and corrosion resistance, extending service life and improving the market Competitiveness.
Patent Information
- Application Number
- CN202411629956.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-18
AI Technical Summary
The surface properties of magnesium-aluminum alloys are unstable, and there are shortcomings in the quality of corrosion resistance and strength. It is difficult for existing surface treatment methods to comprehensively and significantly improve their surface stability.
A treatment method for enhanced magnesium-aluminum alloy is adopted, including surface cleaning treatment, drying treatment, soaking modification treatment and rinsing and insulation treatment. The specific steps include cleaning with alkali liquid, dehydration liquid and deionized water, drying the drying box, energizing the modifier and sonicating it, and finally insulating the heat in the constant temperature box.
This method significantly improves the surface stability of magnesium-aluminum alloy, enhances its wear resistance, weather resistance and corrosion resistance, extends service life, and improves market competitiveness and economic benefits.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnesium-aluminum alloy processing, and in particular relates to a processing method for an enhanced magnesium-aluminum alloy. Background Art
[0002] Magnesium-aluminum alloy has the advantages of low density, high specific strength and specific stiffness, good thermal and electrical conductivity, damping and vibration reduction, electromagnetic shielding, easy processing and forming, and easy recycling of waste. It has important application value in the fields of automobiles, electronic communications, aerospace, national defense and military, and is known as the "green engineering material" of the 21st century.
[0003] Although magnesium-aluminum alloys are easy to form, their surface properties are relatively unstable, and they have shortcomings in corrosion resistance, strength, and other qualities. There are many existing surface treatment methods for magnesium-aluminum alloys, but methods that can comprehensively and significantly improve their surface stability and other qualities are relatively rare. Summary of the invention
[0004] The purpose of the present invention is to provide a method for treating a reinforced magnesium-aluminum alloy.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions: A method for processing an enhanced magnesium-aluminum alloy comprises the following steps: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: Put the magnesium-aluminum alloy treated in step (1) into a drying oven for drying, and take it out after 5 to 7 hours for use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2 to 2.5 hours for use; (4) Flushing and heat preservation treatment: Rinse the magnesium-aluminum alloy treated in step (3) with deionized water, then put the magnesium-aluminum alloy into a constant temperature box and take it out after heat preservation for 3 to 5 hours.
[0006] Furthermore, the alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 4-6%; and the degreasing solution is an acetone solution with a volume fraction of 30-35%.
[0007] Furthermore, during the drying process in step (2), the temperature in the drying oven is controlled to be 100-110°C.
[0008] Furthermore, the modifier described in step (3) is composed of the following substances in corresponding parts by weight: 15-20 parts of zirconium titanium salt, 6-10 parts of acid ion stabilizer, 4-6 parts of sodium chloride, 3-5 parts of phytic acid, 2-4 parts of disodium ethylenediaminetetraacetate, 1-3 parts of polyvinyl alcohol, 5-8 parts of nano magnetic powder, 1-3 parts of sodium dodecylbenzene sulfonate, 3-6 parts of titanate coupling agent, 2-4 parts of nano cellulose, 2-5 parts of sodium carboxymethyl cellulose, and 700-800 parts of deionized water.
[0009] Furthermore, during the power-on treatment in step (3), the applied voltage is controlled to be 28-32V and the current is controlled to be 1-1.5A.
[0010] Furthermore, during the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 600-680 kHz.
[0011] Furthermore, during the heat preservation treatment in step (4), the temperature in the thermostat is controlled to be 70-75°C.
[0012] Furthermore, during the heat preservation treatment in step (4), the constant temperature box is controlled to be a nitrogen environment.
[0013] Compared with the prior art, the present invention has the following advantages: The present invention changes the traditional surface treatment method of magnesium-aluminum alloy, effectively improves the use quality of magnesium-aluminum alloy, wherein the magnesium-aluminum alloy is first subjected to surface cleaning treatment to prepare for subsequent treatment, and then the dried magnesium-aluminum alloy is subjected to special immersion modification treatment, which is the main stage for changing the surface performance of the magnesium-aluminum alloy, and the zirconium-titanium salt, silane coupling agent and other components in the modifier used here can be stably grafted on the surface of the magnesium-aluminum alloy material, and under the action of electric current, they are cross-linked with nano magnetic powder and nano cellulose on the surface of the magnesium-aluminum alloy material, forming a nano magnetic powder, nano cellulose cross-linked filled silane ceramic film composite film, which not only has strong wear resistance and weather resistance stability, but also has high compatible bonding strength with the surface of the magnesium-aluminum alloy, significantly enhances the surface characteristics of the material, and finally eliminates stress after heat preservation treatment, stabilizing the treatment effect. The treatment method of the present invention has the characteristics of green environmental protection and easy promotion, and the treated magnesium-aluminum alloy material has strong corrosion resistance, weather resistance, wear resistance, stable surface quality, significantly long service life, and great market competitiveness and economic benefits. DETAILED DESCRIPTION Example 1
[0014] A method for processing an enhanced magnesium-aluminum alloy comprises the following steps: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: The magnesium-aluminum alloy treated in step (1) is placed in a drying oven for drying and taken out after 5 hours for later use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2 hours for use; (4) Flushing and heat preservation treatment: Rinse the magnesium-aluminum alloy treated in step (3) with deionized water, then put the magnesium-aluminum alloy into a constant temperature box and take it out after heat preservation for 3 hours.
[0015] The alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 4%; the degreasing solution is an acetone solution with a volume fraction of 30%.
[0016] During the drying process described in step (2), the temperature in the drying oven is controlled to be 100°C.
[0017] The modifier described in step (3) is composed of the following substances in corresponding parts by weight: 15 parts of zirconium titanium salt, 6 parts of acid ion stabilizer, 4 parts of sodium chloride, 3 parts of phytic acid, 2 parts of disodium ethylenediaminetetraacetate, 1 part of polyvinyl alcohol, 5 parts of nano magnetic powder, 1 part of sodium dodecylbenzene sulfonate, 3 parts of titanate coupling agent, 2 parts of nano cellulose, 2 parts of sodium carboxymethyl cellulose, and 700 parts of deionized water.
[0018] During the power-on treatment described in step (3), the applied voltage is controlled to be 28V and the current is controlled to be 1A.
[0019] During the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 600 kHz.
[0020] During the heat preservation treatment described in step (4), the temperature in the thermostat is controlled to be 70°C.
[0021] During the heat preservation treatment described in step (4), the constant temperature box is controlled to be a nitrogen environment. Example 2
[0022] A method for processing an enhanced magnesium-aluminum alloy comprises the following steps: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: The magnesium-aluminum alloy treated in step (1) is placed in a drying oven for drying and taken out after 5 hours for later use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2.3 hours for use; (4) Flushing and heat preservation treatment: The magnesium-aluminum alloy treated in step (3) is rinsed with deionized water, and then the magnesium-aluminum alloy is placed in a constant temperature box and taken out after heat preservation treatment for 4 hours.
[0023] The alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 5%; the degreasing solution is an acetone solution with a volume fraction of 30%.
[0024] During the drying process described in step (2), the temperature in the drying oven is controlled to be 100°C.
[0025] The modifier described in step (3) is composed of the following substances in corresponding parts by weight: 15 parts of zirconium titanium salt, 8 parts of acid ion stabilizer, 5 parts of sodium chloride, 4 parts of phytic acid, 2 parts of disodium ethylenediaminetetraacetate, 1 part of polyvinyl alcohol, 5 parts of nano magnetic powder, 1 part of sodium dodecylbenzene sulfonate, 5 parts of titanate coupling agent, 3 parts of nano cellulose, 4 parts of sodium carboxymethyl cellulose, and 750 parts of deionized water.
[0026] During the power-on treatment described in step (3), the applied voltage is controlled to be 28V and the current is controlled to be 1.3A.
[0027] During the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 640 kHz.
[0028] During the heat preservation treatment described in step (4), the temperature in the thermostat is controlled to be 72°C.
[0029] During the heat preservation treatment described in step (4), the constant temperature box is controlled to be a nitrogen environment. Example 3
[0030] A method for processing an enhanced magnesium-aluminum alloy comprises the following steps: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: The magnesium-aluminum alloy treated in step (1) is placed in a drying oven for drying and taken out after 6 hours for later use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2.3 hours for use; (4) Flushing and heat preservation treatment: The magnesium-aluminum alloy treated in step (3) is rinsed with deionized water, and then the magnesium-aluminum alloy is placed in a constant temperature box and taken out after heat preservation treatment for 4 hours.
[0031] The alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 5%; the degreasing solution is an acetone solution with a volume fraction of 33%.
[0032] During the drying process described in step (2), the temperature in the drying oven is controlled to be 105°C.
[0033] The modifier described in step (3) is composed of the following substances in corresponding parts by weight: 18 parts of zirconium titanium salt, 8 parts of acid ion stabilizer, 5 parts of sodium chloride, 4 parts of phytic acid, 3 parts of disodium ethylenediaminetetraacetate, 2 parts of polyvinyl alcohol, 6 parts of nano magnetic powder, 2 parts of sodium dodecylbenzene sulfonate, 5 parts of titanate coupling agent, 3 parts of nano cellulose, 4 parts of sodium carboxymethyl cellulose, and 750 parts of deionized water.
[0034] During the power-on treatment described in step (3), the applied voltage is controlled to be 28~32V and the current is controlled to be 1.3A.
[0035] During the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 660 kHz.
[0036] During the heat preservation treatment described in step (4), the temperature in the thermostat is controlled to be 72°C.
[0037] During the heat preservation treatment described in step (4), the constant temperature box is controlled to be a nitrogen environment. Example 4
[0038] A method for processing an enhanced magnesium-aluminum alloy comprises the following steps: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: Put the magnesium-aluminum alloy treated in step (1) into a drying oven for drying, and take it out after 7 hours for use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2.5 hours for use; (4) Flushing and heat preservation treatment: Rinse the magnesium-aluminum alloy treated in step (3) with deionized water, then put the magnesium-aluminum alloy into a constant temperature box and take it out after heat preservation for 5 hours.
[0039] The alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 6%; the degreasing solution is an acetone solution with a volume fraction of 35%.
[0040] During the drying process described in step (2), the temperature in the drying oven is controlled to be 110°C.
[0041] The modifier described in step (3) is composed of the following substances in corresponding parts by weight: 20 parts of zirconium titanium salt, 10 parts of acid ion stabilizer, 6 parts of sodium chloride, 5 parts of phytic acid, 4 parts of disodium ethylenediaminetetraacetate, 3 parts of polyvinyl alcohol, 8 parts of nano magnetic powder, 3 parts of sodium dodecylbenzene sulfonate, 6 parts of titanate coupling agent, 4 parts of nano cellulose, 5 parts of sodium carboxymethyl cellulose, and 800 parts of deionized water.
[0042] During the power-on treatment described in step (3), the applied voltage is controlled to be 32V and the current is controlled to be 1.5A.
[0043] During the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 680 kHz.
[0044] During the heat preservation treatment described in step (4), the temperature in the thermostat is controlled to be 75°C.
[0045] During the heat preservation treatment described in step (4), the constant temperature box is controlled to be a nitrogen environment.
[0046] After the commercially available AM50A magnesium-aluminum alloy plate was treated by the methods of the above-mentioned embodiments 1 to 4, the performance of its surface film layer was tested, and it was found that the bonding strength between its surface film layer and the material matrix was very high and met the 1 mm 100-grid test.
[0047] After the commercially available AM60B magnesium-aluminum alloy plate was treated by the methods of Examples 1 to 4 above, it was continuously immersed in a 3.5% neutral NaCl solution for 720 hours according to the salt spray test requirements. The surface film layer did not bubble, crack or fall off, and the performance was stable.
[0048] It can be seen from the above that the method of the present invention can significantly improve the stability of the surface of the magnesium-aluminum alloy and extend its service life, and has great promotion and application value and market competitiveness.
Claims
1. A method for treating an enhanced magnesium-aluminum alloy, characterized in that: The steps include: (1) Surface cleaning: The surface of the magnesium-aluminum alloy is cleaned with alkaline solution, degreasing solution and deionized water in sequence; (2) Drying treatment: Put the magnesium-aluminum alloy treated in step (1) into a drying oven for drying, and take it out after 5 to 7 hours for use; (3) Soaking modification treatment: The magnesium-aluminum alloy treated in step (2) is immersed in a modifier for modification, during which the modifier is energized and ultrasonically treated, and the magnesium-aluminum alloy is taken out after 2 to 2.5 hours for use; (4) Flushing and heat preservation treatment: Rinse the magnesium-aluminum alloy treated in step (3) with deionized water, then put the magnesium-aluminum alloy into a constant temperature box and take it out after heat preservation for 3 to 5 hours.
2. A method for processing an enhanced magnesium-aluminum alloy according to claim 1, characterized in that: The alkali solution in step (1) is a sodium hydroxide solution with a mass fraction of 4-6%; the degreasing solution is an acetone solution with a volume fraction of 30-35%.
3. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: During the drying process described in step (2), the temperature in the drying oven is controlled to be 100-110°C.
4. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: The modifier described in step (3) is composed of the following substances in corresponding parts by weight: 15-20 parts of zirconium titanium salt, 6-10 parts of acid ion stabilizer, 4-6 parts of sodium chloride, 3-5 parts of phytic acid, 2-4 parts of disodium ethylenediaminetetraacetate, 1-3 parts of polyvinyl alcohol, 5-8 parts of nano magnetic powder, 1-3 parts of sodium dodecylbenzene sulfonate, 3-6 parts of titanate coupling agent, 2-4 parts of nano cellulose, 2-5 parts of sodium carboxymethyl cellulose, and 700-800 parts of deionized water.
5. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: During the power-on treatment described in step (3), the applied voltage is controlled to be 28~32V and the current is controlled to be 1~1.5A.
6. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: During the ultrasonic treatment in step (3), the frequency of the ultrasonic wave is controlled to be 600-680 kHz.
7. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: During the heat preservation treatment described in step (4), the temperature in the thermostat is controlled to be 70-75°C.
8. The method for processing a reinforced magnesium-aluminum alloy according to claim 1, characterized in that: During the heat preservation treatment described in step (4), the constant temperature box is controlled to be a nitrogen environment.